Integration of amplification efficiency in qPCR analysis allows precise and relative quantification of transcript abundance of genes from large gene families using RNA isolated from difficult tissues. (25th August 2017) - Arunraj, Rex; Samuel, Marcus A
Abstract: The performance of the quantitative polymerase chain reaction (qPCR) assay in the analysis of gene expression belonging to multigene families in tissues rich in secondary metabolites is technically complicated. Here, we present the qPCR analysis of PMT2 gene, a predominant member of a multigene family from tobacco, expressed in the root tissues and is involved in the biosynthesis of nicotine. Consequently, we provide insight into the effect of polymerase chain reaction (PCR) amplification efficiency (AE) of reference and target genes of calibrator and test samples on the qPCR assay performance. Obviously, we found PCR AE as a critical indicator of qPCR assay performance involving multigene families and secondary metabolite-rich root tissues of tobacco. The integration of consistent and uniform PCR amplification efficiencies of reference and target genes of the samples into the relative quantification analysis is emphasized.